2018
DOI: 10.3389/fnhum.2018.00069
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speech Repetition Rate on Neural Activation in Healthy Adults: Implications for Treatment of Aphasia and Other Fluency Disorders

Abstract: Functional imaging studies have provided insight into the effect of rate on production of syllables, pseudowords, and naturalistic speech, but the influence of rate on repetition of commonly-used words/phrases suitable for therapeutic use merits closer examination.Aim: To identify speech-motor regions responsive to rate and test the hypothesis that those regions would provide greater support as rates increase, we used an overt speech repetition task and functional magnetic resonance imaging (fMRI) to capture r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…This was somewhat surprising, because if the observed activation increases were indeed associated with the effort and attention required to produce atypical speech, similar patterns of increased activation were expected to occur in the control participants. This interpretation is further supported by the findings on speech rate changes and fluency-inducing conditions in fluent speakers discussed above [3,11,17,18]. One of the potential explanations for this unexpected finding discussed in the De Nil et al [19] paper was that activation changes in the fluent speakers may have been less pronounced and remained sub-threshold because of methodological reasons (use of a lower field strength (1.5T) scanner, sparse scanning, and use of auditory stimuli).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…This was somewhat surprising, because if the observed activation increases were indeed associated with the effort and attention required to produce atypical speech, similar patterns of increased activation were expected to occur in the control participants. This interpretation is further supported by the findings on speech rate changes and fluency-inducing conditions in fluent speakers discussed above [3,11,17,18]. One of the potential explanations for this unexpected finding discussed in the De Nil et al [19] paper was that activation changes in the fluent speakers may have been less pronounced and remained sub-threshold because of methodological reasons (use of a lower field strength (1.5T) scanner, sparse scanning, and use of auditory stimuli).…”
Section: Introductionmentioning
confidence: 60%
“…Brain imaging studies of fluent speakers have greatly advanced our knowledge of the brain areas involved in speech production [1][2][3][4][5]. Combined, these studies have shown that speech production is supported by a network of brain areas that includes the pre-and postcentral gyri, posterior inferior frontal gyri, medial and lateral premotor cortex, anterior insula, superior temporal gyri, posterior planum temporale region, basal ganglia and cerebellum [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prominent hypotheses inform our current understanding of how the brain recovers speech‐motor function after an insult: (1) Recruitment of perilesional cortex to form a new network of regions in the affected hemisphere (the perilesional hypothesis), (2) engagement of homotopic regions and associated fiber tracts in the undamaged hemisphere to facilitate recovery of speech‐motor function, and (3) a combination of both. The “right‐shift hypothesis” is based on the neural redundancy theory that both hemispheres have the capacity to support speech‐motor function, although the degree to which the right hemisphere becomes involved after damage to the left may differ from person to person and/or depend upon factors that are not yet fully understood. Among the potential determinants of which route is chosen and which leads to success, size and site of left‐hemisphere lesions and lesion load of the arcuate fasciculus (AF) or other speech/language‐relevant structures, may be the most important.…”
mentioning
confidence: 99%
“…Whether or not recruitment of the right hemisphere (1) is a sign of “incomplete recovery” or “less effective compensation,”, (2) occurs only as a transient phenomenon during the recovery process, or (3) indicates use of built‐in redundancy to facilitate recovery in case of an insult to the left hemisphere is still a matter of debate.…”
mentioning
confidence: 99%